(3fVO GdEjVGMs - (3GdcGTj Ch GdcGTGfj, eMSf Hf eQJVi Hf ajV Gddg eMehO, J (B1090(3g`s ((3GHf GdUOQ GdTjQGRj YHO Gddgs)
(3ChdgG (B:s
(3GdMeO ddg GdPj cTa Yf eYGde Ojfg HebGd NdGUI QLGdg(B...(3CeG HYO(B...(3deG cGf JYOjd GdQLGd hLQMge hJYQa CMhGdge ehbhaG Ydi JUMjM CSeGFge(B...(3cGf cJGH EjVGM GdGTJHGg aj CSeGA GdQhGI(B...s
(3BNQgG (B:s
(3CHh gGQhf GdSfLj HGdfhf hGdLje bjd Cf GSeg KGHJ Hf JhHI HGdeKfGI GdahbjI Ke GdhGh Ke GdHGA GdehMOI(B...(3ef CQGO GdJWhjd hGdGSJbUGA(B...(3aYdjg HcJGHfG GdcHjQ GdehShe HcTa GdebGd aj eYQaI GdQLGd(B...s
(3aQZ ef JCdjag (B22 (3QeVGf (B1073(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B:(3L(B5(3,U(B290s
(3EjVGM Gdecfhf(B:(3L(B2(3,U(B655s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3GdJGQjNs